Retaining the generation Y workforce in the company : some suggestions for future employers / Roshidi Hassan and Mohd Abdul Kadir Jailani - Hassan, Roshidi (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
This paper aims to discuss about the need for employers to understand Gen Y and eventually assist them to establish strategies or plan of actions to attract, maintain and retain Gen Y in the organization. Gen Y is deemed as being the future workforce having unique characteristics, behaviours and traits as compared to the earlier generations of Gen X and the Baby Boomers. It was found recently that the turnover rate among the Gen Y is high and organizations are trying to find the reasons for such a problem. Recruiting, maintaining and retaining the Gen Y is seen as the new challenge in managing the new breed of human resources. So, this paper provides some insights into the issues and problems, expose some unique characteristics, behaviours and traits of Gen Y, and provide some steps that can be taken by an organization to help them cope with this phenomenon